Ye heart of a man : the domestic life of men in colonial New England - Wilson, Lisa, 1957- (New Haven, Conn. : Yale University Press, 1999)
This book is the first to investigate the everyday lives of men in prerevolutionary America. It looks at men and women in colonial Massachusetts and Connecticut, comparing their experiences in order to understand the domestic environment in which they spent most of their time. Lisa Wilson tells wonderful stories of colonial New England men, addressing the challenges of youth, the responsibilities of adulthood, and the trials of aging. She finds that ideas about patriarchy or nineteenth-century notions of separate spheres for men and women fail to explain the world that these early New England men describe. Patriarchal power, although certainly real enough, was tempered by notions of obligation, duty, and affection. These men created their identities in a multigendered, domestic world. A man was defined by his usefulness in this domestic context; as part of an interdependent family, his goal was service to family and community, not the self-reliant independence of the next century's "self-made" man
Introduction -- To be of use -- A "business for life" -- "It will not injure you" : men and courtship -- Usefulness -- A husband "well-ordered" -- Provider -- "Ye heart of a father" -- The specter of uselessness -- Widower -- "Like an armed man" : retirement and manhood -- Conclusion.
Includes chapter notes with bibliographical references (pages 189-240), and index.
Print version record.
eBooks on EBSCOhost
Keywords: New England -- Social life and customs -- To 1775.; Men -- New England -- Social life and customs -- 18th century; Sex role -- New England -- History -- 18th century; Families -- New England -- 18th century; Man-woman relationships -- New England -- History -- 18th century; Nouvelle-Angleterre -- Mœurs et coutumes -- Jusqu'à 1775.; Hommes -- Nouvelle-Angleterre -- Mœurs et coutumes -- 18e siècle.; Rôle selon le sexe -- Nouvelle-Angleterre -- Histoire -- 18e siècle.; Familles -- Nouvelle-Angleterre -- 18e siècle.; Relations entre hommes et femmes -- Nouvelle-Angleterre -- Histoire -- 18e siècle.; SOCIAL SCIENCE -- Gender Studies; Families; Man-woman relationships; Manners and customs; Men -- Social life and customs; Sex role; New England; Mannen; Dagelijks leven; To 1799; History